If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 3) = 5x + 13 Reorder the terms: 7(3 + x) = 5x + 13 (3 * 7 + x * 7) = 5x + 13 (21 + 7x) = 5x + 13 Reorder the terms: 21 + 7x = 13 + 5x Solving 21 + 7x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 21 + 7x + -5x = 13 + 5x + -5x Combine like terms: 7x + -5x = 2x 21 + 2x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 21 + 2x = 13 + 0 21 + 2x = 13 Add '-21' to each side of the equation. 21 + -21 + 2x = 13 + -21 Combine like terms: 21 + -21 = 0 0 + 2x = 13 + -21 2x = 13 + -21 Combine like terms: 13 + -21 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 2/3n-5/8=7/8 | | 2.4=(3m+4) | | x/2(28-x)-96=0 | | g(3)=9 | | 0.2(x+3)-0.4(x+3)=0.2x-0.6 | | m-64.5=-7.1 | | 64b^3+1=0 | | -27=-253+x | | 13(t-3)+5t=6(3t+5)-8 | | 2/3g=4/9 | | 0=x^3+3x^2-24x-30 | | 28x^2-x-2=0 | | 5x-4=8y-3 | | 5n=20(4+.25) | | x^2+32x-126=0 | | -24=.263+x | | (3+3x)(6-x)=510 | | -39=x-62 | | 3-5(2+4x)=5 | | 12x-5=5x+23 | | 2x^2-x^2+1-4=0 | | 4cos^2x-3cosx=0 | | 5(a-12)-24=3(a+2) | | 2x^3-5x-69=0 | | 1.3(x+2)+5.6=17.3 | | x-3=-.5x+3 | | 5-9x=-4x | | 3z-2z+8= | | 3x+9=-1Y+29 | | 2x^3-5x-9=0 | | 12-42=3(x-2)-9 | | 100=33+x |